Kajian Status Kesuburan Tanah Sawah Untuk Menentukan Anjuran Pemupukan Berimbang Spesifik Lokasi Tanaman Padi Di Kecamatan Manggis - SUARJANA, I WAYAN; SUPADMA, A.A. NYOMAN; ARTHAGAMA, I DEWA MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.4, No.4, Oktober 2015, 2016)
ABSTRACT Study Status of Fertility paddy Soil to Determine Instigation Balanced Fertilization Specific Location Rice Plants in Manggis District This research to determine of soil fertility status in Manggis district and make instigation balanced fertilization specific location on the rice plants accordance with of soil fertility status. This research was conducted survey and test method of soil analyzed in the laboratory of  Soil Science and Environment Faculty of Agriculture, Udayana University with soil chemical properties determination CEC, Cation Saturated, N-total, P 2 O 5 , K 2 O, C-organic, pH and EC. Results the evaluation of soil fertility status in Manggis district, Karangasem regency consists of soil fertility status high contained on land units I, II, III, VI, and soil fertility status being medium found on land unit IV, V, and VII. Instigation of urea without organic matter much as 250 kg ha -1 , with 5 tons of straw ha -1 addition of urea many as 230 kg ha -1 and 2 tons ha -1 cage fertilizer addition of urea fertilizer 225 kg ha -1 . P fertilization on medium soil status much as 75 SP-36 kg ha -1 , and P fertility status high 50 kg SP-36 ha -1 . K fertilizer application of 50 kg ha -1 . Instigation using fertilizer organic rice straw compost the equivalent of 5 tons ha -1 and 2 ton ha -1 cage fertilizer. Keywords : Soil Fertility Status and Instigation Balanced Fertilization Specific    Location.